Analisis Keterkaitan Keterbukaan Perdagangan terhadap Pertumbuhan Ekonomi di 4 Negara Berkembang ASEAN - Lestari, Tri Yuli; Syahri, Hanif Alfi; Zakaria, Rinny Apriliany; Rahajuni, Dijan (Sosio e-Kons, 2025)
Trade openness is one of the key components in driving economic growth. During the period of 1981-2023, there were differences in the level of trade openness in four ASEAN countries (Indonesia, Malaysia, the Philippines, and Thailand). Additionally, GDP growth, exchange rate fluctuations, rising inflation, and inflows of foreign direct investment (FDI) are expected to influence economic growth in these countries. This study aims to analyze the factors affecting economic growth in these countries. The variables used in this research include economic growth, trade openness, FDI, exchange rate, and inflation. The econometric analysis model used is the Error Correction Model (ECM). The results of the study show an Error Correction Term (ECT) coefficient of -0.6268, which is significant at the ? = 5% level, indicating that the model is valid. The conclusions of this study are: (1) In the short term, trade openness and FDI have a significant positive influence, while exchange rate and inflation have a significant negative influence on economic growth; (2) In the long term, inflation and exchange rate have a negative influence, while trade openness and FDI do not have a significant influence on economic growth.